WAYS TO IMPROVE THE DESIGN OF CLASSICAL TRACTORS WITH AUTOMATIC CONTROL SYSTEMS - LIPNITSKIY, ROMAN; RYABOSHAPKA, VADYM (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article examines the modernisation of the agricultural machinery fleet by installing automatic driving systems, which is a key area for improving the efficiency of agricultural production. Modern automated driving technologies, their features and development prospects are analysed. Particular attention is paid to the impact of such systems on tractor productivity, cost reduction and improvement of working conditions for operators.Based on the analysis of literature sources, the main technological advantages of automated driving are identified: increasing the accuracy of operations, reducing the consumption of fuel and lubricants, optimising the use of resources and minimising the impact of the human factor. The economic aspects of implementation are considered, including return on investment, the possibility of modernising equipment and adaptation to different types of farms.The influence of vibrations during the operation of machinery on the stability of RTK correction signals is investigated. Vibration loads can cause temporary deviations in the reception of satellite signals, which affects the positioning accuracy. Methods of compensating for this impact are considered, including the use of damping platforms, signal filtering and software correction algorithms.The technical, economic, and organisational challenges associated with the conversion of tractors are also considered. A comparative analysis of the types of automatic driving systems and their compatibility with existing equipment is carried out. The criteria for selecting optimal solutions for modernisation are determined.Recommendations for the planning and implementation of tractor fleet modernisation projects are proposed, taking into account economic feasibility, technical compatibility and prospects for further automation. The results obtained can be used to introduce innovative technologies in agricultural production in order to increase its efficiency and competitiveness.
Keywords: automatic driving system; tractor; automation; RTK receiver